BENTUK KESULITAN BELAJAR MENULIS SWA KELAS II SEKOLAH DASAR: STUDI PADA SISWA DI SDN 1 PUYUNG, KAB. LOMBOK TENGAH - Niswati, Husnun; Witono, A. Hari; Setiawan, Heri (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
The purpose of this study was to describe the difficulties in learning to write in grade II students at SD Negeri 1 Puyung and to identify the factors causing difficulties in learning to write in grade II. This study used a descriptive qualitative research method using observation, interview and documentation techniques. According to the results of the study, the difficulties in writing in grade II are as follows. The use of capital letters and lowercase letters is still mixed, the size and shape of the letters in the writing are not proportional and inconsistent, it is difficult to hold a pencil firmly. And the following are the factors causing difficulties in learning when starting to write: Factors from students such as slower development compared to peers, IQ, motor development, and cognitive development that may be impaired. External factors that may cause are the lack of support and writing culture from the family as the student's first school.